Case Study: Parenting Use of Digital Technology in Preschool Children by Middle-Class Digital Immigrant Parents - Najmudin, Muhammad Faisal; Sardin, Sardin; Sulistiono, Eko (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
This study explores parents' knowledge of digital technology among the digital immigrant generation, who often face difficulties in utilizing technology, parenting practices for preschool children, and associated challenges. It employs qualitative research through a case study method, conducting interviews with parents born before 1981, having children aged 0-6 years, and falling within the lower-middle-class income bracket. This research was conducted from May to June 2023 in Bandung. From the five informants, it was evident that they possessed various digital devices, including smartphones, televisions, computers, and laptops with internet connections. Despite not growing up with digital technology, these parents utilize smartphones to enhance their children's motor and language development, often through educational videos or entertainment, such as games. Nonetheless, they face challenges and risks, such as children becoming overly reliant on technology and reducing their direct social interaction. In the current digital age, parents play a crucial role in ensuring appropriate and safe digital technology usage for preschool-aged children whose cognitive and functional abilities are still developing. Consequently, these findings emphasize the need for parents to exercise careful supervision of the content accessed by their children, potentially by implementing special rules or restrictions on screen time.